Analysis and assessment of a new solar assisted sodium hydroxide thermochemical hydrogen production cycle - Oruc, Onur; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
In this study, a system integration approach is carried out by conducting research on the Sodium Hydroxide (NaOH) thermochemical cycle, one of the thermochemical water separation and hydrogen production methods. The NaOH thermochemical cycle is performed using Aspen Plus commercial software, the chemical 1D software. The present integrated solar energy system is designed using SAM (System Advisory Model) software. With SAM software?s help, the physical properties of pure energy storage tanks with molten salt are determined. The system is intended to generate hydrogen and electricity for 24 h. The NaOH thermochemical hydrogen production cycle can produce one kmol of hydrogen per second. The thermochemical cycle?s energy and exergy efficiencies are calculated as 80% and 82%, respectively. Overall energy and exergy efficiencies are found as 11% and 13%, respectively.
Keywords: Solar energy; Solar tower; Thermochemical cycle; NaOH; Hydrogen production; Energy; Exergy; Efficiency; Thermodynamics; Energy & Fuels; Mechanics